Prevalence and proportion estimate of asymptomatic Plasmodium infection in Asia: a systematic review and meta-analysis - Kotepui M. (2023)
Asymptomatic Plasmodium infection raises a problem for the persistent transmission of malaria in low-endemic areas such as Asia. This systematic review was undertaken to estimate the prevalence and proportion of asymptomatic Plasmodium infection in Asia. The systematic review was registered at PROSPERO (ID: CRD42022373664). The research followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. A comprehensive search of five databases, Ovid, Scopus, MEDLINE, PubMed, and Embase, was conducted to identify studies of asymptomatic Plasmodium infection in Asian countries. The pooled prevalence of asymptomatic Plasmodium infection, the pooled proportion of asymptomatic Plasmodium infection among all parasitised individuals, and the associated 95% confidence intervals were estimated using a random-effects model. A total of 916 articles were retrieved, and 87 articles that met the criteria were included in the systematic review. The pooled prevalence of asymptomatic Plasmodium infection among enrolled participants in Southeast Asia, South Asia, and Western Asia was 5.8%, 9.4%, and 8.4%, respectively. The pooled proportion of asymptomatic Plasmodium infection among all parasitised individuals in Southeast Asia, South Asia, and Western Asia was 89.3%, 87.2%, and 64.8%, respectively. There was a low prevalence of asymptomatic Plasmodium infection, but there was a high proportion of asymptomatic Plasmodium infection per all parasitised individuals in different parts of Asia. These results may support and facilitate elimination and control programs for asymptomatic Plasmodium infection in Asia.